2001
DOI: 10.1128/jvi.75.21.10090-10105.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Telomeres: Interaction with the Viral I1, I6, and K4 Proteins

Abstract: The 192-kb linear DNA genome of vaccinia virus has covalently closed hairpin termini that are extremely AT rich and contain 12 extrahelical bases. Vaccinia virus telomeres have previously been implicated in the initiation of viral genome replication; therefore, we sought to determine whether the telomeres form specific protein-DNA complexes. Using an electrophoretic mobility shift assay, we found that extracts prepared from virions and from the cytoplasm of infected cells contain telomere binding activity. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Six viral proteins, I6L, G5R, A12L, A14.5, A32L, and B1R, have been cited in the literature as being IMV associated but were not identified in our analyses (Table 3) (19,34,43,48,68,99,160). All six proteins were not detected in LC/MS/MS using different IMV preparations, although three proteins (A12L, A32L, and B1R) were detected in SCX-LC/MS/MS, suggesting that the abundances of these three proteins were below the threshold of LC/MS/MS and that SCX chromatography was necessary to reduce the sample complexity in order to enhance the detection sensitivity (Table 3).…”
Section: Resultsmentioning
confidence: 79%
“…Six viral proteins, I6L, G5R, A12L, A14.5, A32L, and B1R, have been cited in the literature as being IMV associated but were not identified in our analyses (Table 3) (19,34,43,48,68,99,160). All six proteins were not detected in LC/MS/MS using different IMV preparations, although three proteins (A12L, A32L, and B1R) were detected in SCX-LC/MS/MS, suggesting that the abundances of these three proteins were below the threshold of LC/MS/MS and that SCX chromatography was necessary to reduce the sample complexity in order to enhance the detection sensitivity (Table 3).…”
Section: Resultsmentioning
confidence: 79%
“…The molecular mass of I6 is predicted to be 43.5 kDa, and apart from counterparts in other poxviruses, no significant homology to any other proteins was found by computer analysis. Our laboratory confirmed that recombinant I6 protein specifically rec-ognizes extrahelical bases and binds to the viral hairpins with great specificity and stability (6). The work described herein was designed to elucidate the role of I6 in vivo.…”
mentioning
confidence: 70%
“…The vaccinia virus I6 protein first came to our attention because of its ability to bind to the telomeric hairpins of the viral genome with high specificity and stability; this interaction is dependent upon the extrahelical bases that distinguish these unusual telomeres (6). We hypothesized that this protein would be involved in an important facet of genome metabolism, either in the initiation of DNA synthesis or the encapsidation of viral DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I6 is a telomere-binding protein that recognizes extrahelical bases at the hairpin termini of the VACV genome. A suitable DNA structure is essential for the formation of a complex between telomere-binding proteins and the hairpin termini (16). Therefore, it is plausible to suppose that alterations in DNA structure induced by the incorporation of nucleoside analogues could compromise the interaction of DNA with DNA-binding proteins and the subsequent encapsidation of the viral genome.…”
Section: Discussionmentioning
confidence: 99%